Hydrochemical Assessment of Surface and Groundwater in Some Selected Communities of Borno and Yobe State (Global Journal of Science Frontier Research, 2023)
The study area comprises three communities of Ala, Daura in Borno State and Kyalari in Yobe State, North-eastern Nigeria which forms part of the Chad Basin. Twenty five (25) water samples were collected from major sources which comprises of nine (9) hand dug wells, ten (10) surface water and six (6) boreholes. The physical parameters analyzed revealed pH values ranging from 6.5 -8.1 and electrical conductivity varies between 67 -1050mµ/cm. The results of the chemical parameters shows that Ca2+ ranges between 3.5 to 66.5mg/l, while Mg2+ varies from 4.8 to 28.2mg/l, Na+ and K+ varies between 0.7 to 1241.0mg/l and2.0 to 112.0mg/l respectively. HCO3-ranges from 77.5mg/l to 337.0mg/l while Cl-varies from 4.0 to 160.0mg/l. The concentration of SO4-varies between 0.7mg/l to 283.0mg/l. This study confirms that they are normal for domestic, agricultural and small scale irrigation purposes. The study shows that some cation and anion are within WHO limits of 2020 permissible limit of drinking water standard except for WARODI wells which show abnormally higher values above the WHO standard.
Keywords: surface water; groundwater; concentration; communities; boreholes; hand dug wells and warodi